THE EFFECTIVENESS OF IMPLEMENTING LISTENING JOURNALS ON THE DEVELOPMENT OF STUDENTS’ ACTIVE LISTENING - Dian Saputra; Muhaiminah Akib; Rezkiah Hartanti (IKIP Siliwangi, 2022)
The purpose of this research is to present the reader with an overview of students’ understanding of the use of listening journal (LJ) media in the development of students’ listening ability. The researcher employs descriptive qualitative techniques and collects data via the use of questionnaires and interviews. The participants in this research were thirty students from the fourth semester of the English Education Department at Universitas Muhammadiyah Sorong. Due to the implementation of LJ practice, participants must watch videos of a speaker’s narrative of information to complete the process. Then, start with constructing and summarizing the elements that will be included in the LJ template. Findings from this research include the capacity of students to complete LJ and the hurdles they face. First and importantly, the findings show that certain students’ abilities, such as listening, pronunciation, vocabulary, and English speaking have improved. The second result is that there were hurdles to finished LJ, such as difficulty completed LJ, pronunciation that was too fast, an accent, and a video that is much too lengthy in duration. In order for the findings guide to future researchers who want to investigate the same research topic in greater depth using various samples and tools. Keywords: Listening Journal, Active Listening, Listening Skill